Integrated Productive Waqf Management: The Halal Tourism Ecosystem Model on Land of Waqf Teras Lembang - Lu'liyatul Mutmainah; Listia Andani; Angga Yogaswara; Akbar Rizqi Kurniawan (JESI (Jurnal Ekonomi Syariah Indonesia), 2026)
Puprose: This study aims to analyze the implementation of management principles and best practices, challenges, and opportunities faced in the development of integrated productive waqf on the Land of Waqf Teras Lembang managed by the Sinergi Foundation. Methodology: This research employs a qualitative approach, utilizing NVivo 12 software for analysis. The research will be conducted through interviews, documentation, and observation. Results: The research results show that the Sinergi Foundation's management of productive waqf in the Land of Wakaf Teras Lembang has implemented integrated management, from planning and administration to implementation and supervision, effectively and collaboratively. The main challenges include licensing, public trust, and controlling, but development opportunities are wide open with regulatory support and increased public awareness. Conclusion: This research provides an overview of the best practices for productive waqf management especially for halal tourism development with potential market of 12% from 6 million visitors in Lembang. Implication: This study cannot be generalized to represent the entire productive waqf. Further research can use a more comprehensive analysis with a mix method and the improvement of productive waqf literacy should be synergized between stakeholders Originality: This study provides a comprehensive analysis through in-depth interviews using NVivo regarding productive waqf-based halal tourism.